2015
DOI: 10.4172/2161-0703.1000185
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Metapneumovirus in Hospitalized Children with Acute Respiratory Tract Infections in Sulaimani Province, Iraq

Abstract: Background: Human Metapneumovirus (hMPV) is a member of Paramyxoviridae family. It is an important viral pathogen of respiratory tract infections among children. Therefore, the aim of this study is to determine the incidence of hMPV infections among children less than 5 years of age with respiratory tract infections at the pediatric hospital in Sulaimani city of Iraq. Also, this study aims to evaluate the different diagnostic methods for the detection of this virus.Method: Nasopharyngeal swabs and throat swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
2
1
Order By: Relevance
“…Fever is generally more widespread among children with respiratory tract infection, this result in agreement with previous study done by Aziz et al, (2015) reported fever and wheezing were more common clinical sign in children with hMPV [14]. While Ji Wang, et al, (2009) found fever, cough, and rhinorrhea were more common than other signs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Fever is generally more widespread among children with respiratory tract infection, this result in agreement with previous study done by Aziz et al, (2015) reported fever and wheezing were more common clinical sign in children with hMPV [14]. While Ji Wang, et al, (2009) found fever, cough, and rhinorrhea were more common than other signs.…”
Section: Discussionsupporting
confidence: 90%
“…Data obtained from this study indicate that most positive patients of RSV from urban area and exactly 39(72.22%), (Table 2), this result which agreed to similar study that has reported increased infections in Kurdistan region of Iraq [32]. In contrast, this result disagreed with a study done by Aziz (2015) to detect hMPV [14]. The reason of high prevalence in the urban residence could be related to crowded and bad hygiene in the large cities.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the HMPV positivity rate was significantly higher during season II compared to season I. it is definitely recognized that respiratory tract infections are one of the biggest health problems experienced by Iraqi health authorities, particularly among infants and children. However, limited studies were conducted in Iraq concerning the rate of HMPV infection, for instance, in Baghdad, two studies were reported controversial rates of hMPV (1.33% and 16%) respectively, while in Iraqi-Kurdistan, the rate of HMPV infection among children suffering from respiratory diseases and flu-like illness was high as compared with the results of current study (13.4% to 29.74%) (19,20,21,22) . Undoubtedly, Studies from around the world had yielded variable detection rates of HMPV, for example in Bangkok, Pakistan, Norway and Brazil, the HMPV was detected among hospitalized children with RTIs in (3.6%, 7%, 7.3% and 20%) respectively (23,24,25,26) .…”
Section: Discussioncontrasting
confidence: 82%
“…In Kuala Lumpur-Malaysia, a higher detection rate of HMPV was documented in March 2012, April and November 2013 (31) . Previous studies from Egypt, Kurdistan, and Pakistan, showed that the majority of hMPV infection was detected in the winter months with peak rates in February (32,19,33) .The high detection rates of HMPV during the second season may be partly due to the sharp change in climate and to the type of collected specimens.…”
Section: Discussionmentioning
confidence: 90%